PEGylated Elastic Liposomal Formulation for Lymphatic Targeting of Zidovudine - Jain, Subheet; Tiwary, A. K.; Jain, N. K. (Current Drug Delivery, 2008)
The present study was aimed at in vitro and in vivo evaluation of PEGylated elastic liposomal formulation for lymphatic targeting of zidovudine (AZT). PEGylated elastic liposomal formulation was prepared and characterized for characteristic in vitro, ex-vivo and in vivo parameters. The plain and PEGylated elastic liposomal formulation showed transdermal flux of 99.8±5.8 and 119.5±5.2 μg/cm2/hr, respectively across the rat skin. Results of biodistribution study indicated 27-fold higher accumulation of AZT in lymphoid tissues after application of PEGylated elastic liposomes as compared to free drug. The efficient localization of elastic liposomal formulation in lymphatic system is of particular interest for HIV therapy, taking in account that replication of HIV mainly takes place in the lymphoid system. The Cellular uptake studies showed significantly higher cellular uptake in lymphoid cells (MT-2 cell line) from PEGylated elastic liposomal formulation (88.9±8.7%) in comparison to phosphate buffer saline (PBS, pH 7.4) solution of drug (27.1±2.8%). The entrapment of AZT into PEGylated elastic liposomes represents a potential approach for overcoming the toxicity by its selective uptake in lymphoid organs. This represents attractive approach for sustained and targeted delivery of AZT.
Keywords: lymphatic uptake